The Effect of Back Massage on Increasing Breast Milk Production: Scoping Review - Sri Putriani Sinaga; Mufdlilah Mufdlilah (Poltekita : Jurnal Ilmu Kesehatan, 2023)
Exclusive breastfeeding begins within one hour after birth until the baby is six months old. Early initiation of breastfeeding and exclusive breastfeeding can help children survive and have antibodies to protect against common diseases, such as diarrhea and pneumonia. Breastfed children perform better on intelligence tests and are less likely to develop obesity and diabetes. This scoping review aims to review the evidence base regarding the effect of back massage on increasing milk production. Inclusion criteria: the criteria included in this review were Indonesian or English articles published within the last five years. These articles focused on the effect of back massage on increasing milk production. The method that will be used in this review is the scoping review technique, which is a systematic exploratory method by mapping the available literature in an article, topics, theories, and sources that have been obtained. The results of the study show that back massage can increase milk production. The most dominant factor in increasing milk production was in the group that did back massage, while the control group did not experience smooth milk production due to a lack of increase in milk production. Increased milk production can also be influenced by nutrition, rest, baby sucking, and breast care performed by the mother.